2011
DOI: 10.1111/j.1600-0722.2011.00851.x
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of acetylcholine-mediated endothelium-dependent relaxation in isolated parotid artery of the alloxan-induced diabetic rabbit

Abstract: The aim of this study was to assess the effect of type 1 diabetes mellitus (induced by a single intravenous injection of 100 mg kg(-1) of alloxan) on acetylcholine (ACh)-induced relaxation in isolated rabbit parotid gland feeding artery. Isometric force measurements and quantification of inducible nitric oxide synthase (iNOS) mRNA by real-time RT-PCR were made in parotid artery rings from diabetic and control rabbits. Acetylcholine induced concentration- and endothelium-dependent vasorelaxation that was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
2
3
0
Order By: Relevance
“…These results suggest that M 3 receptors, not only on the secretory cells, but most likely on the blood vessels also, are involved in the carbachol secretory response in the rabbit parotid gland. This is in accordance with already established involvement of M 3 receptor‐mediated vasodilation in the parotid artery, main feeding artery for rabbit parotid gland which contributes to secretion (Roganović et al , ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results suggest that M 3 receptors, not only on the secretory cells, but most likely on the blood vessels also, are involved in the carbachol secretory response in the rabbit parotid gland. This is in accordance with already established involvement of M 3 receptor‐mediated vasodilation in the parotid artery, main feeding artery for rabbit parotid gland which contributes to secretion (Roganović et al , ).…”
Section: Discussionsupporting
confidence: 92%
“…These results indicate that DM differently affects NOS isoforms involved in the muscarinic M 3 receptor‐mediated secretion: iNOS was upregulated, playing the main role in mediating reduced parotid secretion under DM, and nNOS was unchanged, while eNOS was downregulated. It is interesting to note that in diabetic rabbit parotid artery, feeding artery for parotid gland, impaired endothelium‐dependent vasorelaxation to acetylcholine appears to be due to a loss of NO deriving from eNOS, but not to alteration at M 3 receptor level (Roganović et al , ). Having in mind that vasodilation significantly contributes to secretion in salivary glands, it seems that reduced salivary secretion under DM could be attributed, at least in part, to the impairment of blood supply.…”
Section: Discussionmentioning
confidence: 99%
“…Our spare receptor hypothesis was supported by an estimated four-fold lower k GB-83 in PAR2-HET compared to PAR2-WT, which indicates there are fewer spare receptors in PAR2-HET. The methods that we used to quantitatively estimate the spare receptors in aortas of PAR2-HET and PAR-WT are considered classical pharmacological approaches and have been used to examine other seven transmembrane G-protein coupled receptors [18], [21]. While the concept of spare receptors aligns with our observations and offers one explanation for the closer resemblance of PAR2-HET to PAR2-WT than to PAR2-KO, it does exclude other possible mechanisms.…”
Section: Discussionsupporting
confidence: 65%
“…Two data points in PAR2-WT were excluded because these were considered as being outliers of the linear regression scatter plots (dispersion outside the 95% confidence intervals for the slopes). Equilibrium binding constants for GB-83 ( k GB-83 ) were calculated from 1/slope as determined by a regression of the Schild equation [18], [19] defined by the formula: ( r A −1) = (1/ k GB-83 )[GB-83]+intercept; where r A is defined as the ratio of agonist (2fly) EC 50 in the presence of antagonist (GB-83) to agonist EC 50 in the absence of inhibitor. For mRNA expression data, statistical comparisons were made using REST software as previously described [6].…”
Section: Methodsmentioning
confidence: 99%
“…The influence of dysfunctional autonomic nervous system in non‐insulin‐dependent diabetes mellitus patients was indicated by correlation between stimulated saliva secretion and heart rate sympathetic and parasympathetic components variability (Meurman et al , ). Having in mind, the significance of blood flow to salivary secretion, recent study on experimentally induced diabetes demonstrated decreased vasorelaxant response to acetylcholine, due to endothelial dysfunction, in the rabbit feeding artery of parotid gland (Roganović et al , ). Also, direct evidence of impaired salivary function in non‐insulin dependent diabetes mellitus patients was established by quantitative salivary scintigraphy (Lin et al , ).…”
Section: Discussionmentioning
confidence: 99%